2019
DOI: 10.3390/ijerph17010141
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate Esters and Their Potential Risk in PET Bottled Water Stored under Common Conditions

Abstract: A great deal of attention has been paid lately to release of phthalate esters (PAEs) from polyethylene terephthalate (PET) bottles into PET bottled drinking water due to their potential endocrine-disrupting effects. Three kinds of PAEs, including diethyl phthalate (DEP), dimethyl phthalate (DMP) and dibutyl phthalate (DBP), were detected in 10 popular brands of PET bottles in Beijing, ranging from 101.97 μg/kg to 709.87 μg/kg. Meanwhile, six kinds of PAEs, including DEP, DMP, DBP, n-butyl benzyl phthalate (BBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…) was below the acceptable risk level of 10 -6 , suggesting the carcinogenic health risk is extremely low for consumers exposed to this compound in the bottled drinking water brands in Delta State, which is concurrent with the findings of Jeddi et al [33], Li et al [38] and Xu et al [4].…”
Section: Health Risk Assessmentsupporting
confidence: 82%
See 1 more Smart Citation
“…) was below the acceptable risk level of 10 -6 , suggesting the carcinogenic health risk is extremely low for consumers exposed to this compound in the bottled drinking water brands in Delta State, which is concurrent with the findings of Jeddi et al [33], Li et al [38] and Xu et al [4].…”
Section: Health Risk Assessmentsupporting
confidence: 82%
“…Polyethylene terephthalate (PET) is a thermoplastic polymer widely used in commercial bottles for drinking water due to its cheaper cost of production [2]. However, studies have shown that PET bottling could leach endocrine disruptors such as phthalate acid esters (PAEs) under daily use conditions [3,4]. PAEs are nonreactive plasticizers, produced industrially and used in the manufacture of plastics to increase their durability, transparency, flexibility, and longevity [5].…”
Section: Introductionmentioning
confidence: 99%
“…These phthalate plasticizers are used in hundreds of products in our homes, hospitals, cars, and businesses, such as vinyl flooring, plastic packaging, toys, medical tubing, and cosmetics [ 3 , 4 , 5 , 6 , 7 ]. For example, Xu et al (2020) reported the sum concentrations of dimethyl phthalate (DMP), diethyl phthalate (DEP), and dibutyl phthalate (DBP) ranged from 102 to 710 µg/kg in polyethylene terephthalate (PET) bottles collected from Beijing, China [ 8 ]. PAEs are not covalently bound to the plastic [ 9 , 10 ], so they can be easily released into the environment, leading to potential human exposure through ingestion, dermal absorption, and inhalation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of plastic packaging for food and beverages has shifted cans and glass packaging significantly because plastic packaging is easy to produce, easy to obtain, lightweight to carry, and cheap. Drinking water stored in bottles of the polyethylene terephthalate (PET) type has become popular because it is easy to use and inexpensive [1]. Three types of phthalate esters (PAEs), dibutyl phthalate (DBP), diethyl phthalate (DEP), and di (2-Ethylhexyl) phthalate (DEHP), have been detected in bottled PET [1] [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…Drinking water stored in bottles of the polyethylene terephthalate (PET) type has become popular because it is easy to use and inexpensive [1]. Three types of phthalate esters (PAEs), dibutyl phthalate (DBP), diethyl phthalate (DEP), and di (2-Ethylhexyl) phthalate (DEHP), have been detected in bottled PET [1] [2] [3]. DEHP is most commonly used as a plastic material because it is strong and waterproof but can contaminate water when exposed to heat and stored for a long time [4].…”
Section: Introductionmentioning
confidence: 99%